Migration, Conflict and Internal Displacement in North-East India: A Study with Focus on Conflict-Induced Internal Displacement of Nepalis and Bengalis in Assam - Rayhan, Dewan Abu (International Journal of Multidisciplinary Approach Research and Science, 2025)
In actuality, the term "migration" refers to the process of moving from one location to another; it can be either temporary or permanent, and it is influenced by several determinants, including social, economic, political, and environmental variables. During the colonial and post-colonial eras, a vast number of migrants arrived in northeastern India. At the same time, its effects have been felt in this area's society. In particular, the state of Assam has had numerous instances of strife or ethnic clash, primarily between the local population and migrant communities (Bengali and Nepali) since independence. Ethnic violence has frequently targeted migrant communities, sending them back to their home countries as illegal immigrants or doubtful citizens. Despite having lived in the state for a long time and assimilated into Assam's mainstream multicultural community, they have often been labelled as aliens because of their figures, which have raised concerns in the area. In addition, they have experienced internal displacement and widespread evictions. This study examines the displacement of Bengalis and Nepalis in northeastern India due to war, with a particular emphasis in Assam. The study also examines institutional and governmental perspectives about rehabilitation and aiding these internally displaced victims.